Деякі питання визначення правового статусу митних посередників в Україні - Міщенко, Ілона Володимирівна; Мищенко, Илона Владимировна; Mishhenko, Ilona (My University, 2011)
The article is dedicated to the general principles of enterprises providing intermediary customs services. The author mentions the features and characters of customs intermediaries. Peculiarity of their legal status and causing factors are researched. The author's definition of category «customs intermediary» is given.
Міщенко І. В. Деякі питання визначення правового статусу митних посередників в Україні / І. В. Міщенко // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 345-350.
Keywords: митний посередник; митна справа; посередницька діяльність; таможенный посредник; таможенное дело; посредническая деятельность; customs broker; customs business; agency business